Nocardioides ferulae sp. nov., isolated from root of an endangered medicinal plant Ferula songorica Pall. ex Spreng. Issue 5 (8th February 2019) - Liu, Yong-Hong; Fang, Bao-Zhu; Mohamad, Osama Abdalla Abdelshafy; Zhang, Yong-Guang; Jiao, Jian-Yu; Dong, Zhou-Yan; Xiao, Min; Li, Li; Li, Wen-Jun
Abstract : A novel endophytic bacterium, designated strain SZ4R5S7 T, was isolated from surface-sterilized root of an endangered medicinal plant ( Ferula songorica Pall. ex Spreng) collected from Xinjiang, north-west China. The taxonomic position of the strain was investigated by using a polyphasic approach. The strain was found to be aerobic, Gram-stain-positive, oxidase-negative and catalase-positive, short rods and non-motile. Strain SZ4R5S7 T grew at 4–37 °C (optimum, 28 °C), pH 5.0–9.0 (pH 6.0–8.0) and in the presence of 0–4 % (w/v) NaCl. The polar lipids detected for strain SZ4R5S7 T were phosphatidylglycerol, diphosphatidylglycerol, phosphatidylinositol and two unidentified lipids. The predominant menaquinone of strain SZ4R5S7 T was MK-8(H4 ), and the major fatty acids were iso-C16 : 0 and anteiso-C14 : 0 . The DNA G+C content was determined to be 72.4 mol%. Phylogenetic analysis based on the 16S rRNA gene sequence indicated that strain SZ4R5S7 T belongs to the genus Nocardioides and showed highest levels of 16S rRNA gene sequence similarity to members of the strain Nocardioides kribbensis KSL-2 T (97.8 %). On the basis of phenotypic, genotypic and phylogenetic data, strain SZ4R5S7 T represents a novel species in the genus Nocardioides, for which the name Nocardioides ferulae sp. nov. is proposed and the type strain is SZ4R5S7 T (=CGMCC 4.7456 T =KCTC 39994 T ).